2010
DOI: 10.1002/cbic.201000166
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Novel Peptidic DnaK Ligands

Abstract: The hsp70 chaperone DnaK from E. coli plays a major role in cellular stress response and is involved in assisted protein folding in vivo. By screening a combinatorial peptide library, we identified several DnaK‐specific peptide ligands with nanomolar affinities, which are able to inhibit the secondary amide peptide bond cis/trans isomerase (APIase) activity of DnaK, as well as DnaK/DnaJ/GrpE‐assisted refolding of firefly luciferase. Our designed DnaK inhibitors have the capability to penetrate E. coli cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 59 publications
(97 reference statements)
1
14
0
Order By: Relevance
“…In light of these facts, several laboratories have recently designed and optimised novel proline-rich AMP analogues with interesting antibacterial activities and with no toxic effects on mammalian cell lines or erythrocytes [7][8][9]. The high proline content also provides fairly good stability against proteolytic degradation in mammalian serum, which can be even further reduced by stabilising the cleavage sites.…”
Section: Introductionmentioning
confidence: 99%
“…In light of these facts, several laboratories have recently designed and optimised novel proline-rich AMP analogues with interesting antibacterial activities and with no toxic effects on mammalian cell lines or erythrocytes [7][8][9]. The high proline content also provides fairly good stability against proteolytic degradation in mammalian serum, which can be even further reduced by stabilising the cleavage sites.…”
Section: Introductionmentioning
confidence: 99%
“…These values correspond to binding constants reported for other DnaK-binding sequences, ranging from 0.1 to 10 mm. [14] Cocrystallization of oncocin O2 with the substrate binding domain of DnaK (residues 389 to 607), demonstrated that oncocin residues 4 to 10 (PPYLPR) bound to the peptide binding site of DnaK, whereas the remaining terminal residues of the peptide were flexible (Figures 1 and S4-S8). [15] Interestingly, this sequence stretch matched the residues identified by the Ala-scan as crucial for antibacterial activity.…”
mentioning
confidence: 96%
“…Oncocin was digested between 15 R and 16 I (Figure 2). The two shorter peptides ( [1][2][3][4][5][6][7][8][9][10][11][12][13] O2 and [1][2][3][4][5][6][7][8][9][10] O2) with a C-terminal Pro were probably the results of degradation of [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] O2 by exoproteases. Peptide O2 was slightly more stable (t1 = 2 = 125 min), but also cleaved before Ile16.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Other factors which are essential for an efficient use of an AMP are its membrane penetration, serum stability, and half-life in an organism. All of these factors can be influenced by slight modifications in the amino acid sequences of AMPs [6], and relatively subtle amino acid substitutions have been shown to dramatically improve the antimicrobial activity of oncocin derivatives in certain cases [7,8]. However, the redesign of a peptide of, e.g., 20 amino acids in length, is a complex and timeconsuming task as theoretically every amino acid position can be replaced with every existing naturally occurring and synthetic amino acid.…”
Section: Introductionmentioning
confidence: 99%